Family Structure and the Education Gender Gap: Evidence from Italian Provinces - Graziella Bertocchi; Monica Bozzano (Institute for the Study of Labor (IZA), 2014)
We investigate the determinants of the education gender gap in Italy in historical perspective with a focus on the influence of family structure. We capture the latter with two indicators: residential habits (nuclear vs. complex families) and inheritance rules (partition vs. primogeniture). After controlling for economic, institutional, religious, and cultural factors, we find that over the 1861-1901 period family structure is a driver of the education gender gap, with a higher female to male enrollment rate ratio in upper primary schools being associated with nuclear residential habits and equal partition of inheritance. We also find that only the effect of inheritance rules persists over the 1971-2001 period.
Keywords: E02; H75; I25; J16; N33; O15; 330; education gender gap; Italian Unification; family types; inheritance; institutions; religion; convergence